2014
DOI: 10.3390/molecules19022049
|View full text |Cite
|
Sign up to set email alerts
|

Three New Clerodane Diterpenes from Polyalthia longifolia var. pendula

Abstract: Three new clerodane diterpenes, (4→2)-abeo-cleroda-2,13E-dien-2,14-dioic acid (1), (4→2)-abeo-2,13-diformyl-cleroda-2,13E-dien-14-oic acid (2), and 16(R&S)-methoxycleroda-4(18),13-dien-15,16-olide (3), were isolated from the unripe fruit of Polyalthia longifolia var. pendula (Annonaceae) together with five known compounds (4-8). The structures of all isolates were determined by spectroscopic analysis. The anti-inflammatory activity of the isolates was evaluated by testing their inhibitory effect on NO producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Polyalthia longifolia extracts and their isolated compounds observed in this study to the presence of clerodane diterpenes, of which the closed lactone form, HDK-20, was more active against the kinetoplastids than the aldehyde or carboxylic acid moieties on the scaffold. HDK-20 and HDK-79 have previously been described in extracts of P. longifolia, with antifeedant (Phadnis et al, 1988) and anti-inflammatory properties (inhibition of NO production by macrophages; Wu et al, 2014). Wink (2008) reported that lipophilic secondary metabolites like the terpenoids have detergentlike properties that can disrupt biological membranes, alter their fluidity and inhibit the function of membrane proteins, including those involved in cellular signaling and transport.…”
Section: Discussionmentioning
confidence: 99%
“…Polyalthia longifolia extracts and their isolated compounds observed in this study to the presence of clerodane diterpenes, of which the closed lactone form, HDK-20, was more active against the kinetoplastids than the aldehyde or carboxylic acid moieties on the scaffold. HDK-20 and HDK-79 have previously been described in extracts of P. longifolia, with antifeedant (Phadnis et al, 1988) and anti-inflammatory properties (inhibition of NO production by macrophages; Wu et al, 2014). Wink (2008) reported that lipophilic secondary metabolites like the terpenoids have detergentlike properties that can disrupt biological membranes, alter their fluidity and inhibit the function of membrane proteins, including those involved in cellular signaling and transport.…”
Section: Discussionmentioning
confidence: 99%
“…Clerodane diterpenes can induce apoptosis in human leukemia HL-60 cells [ 98 ]. Moreover, 16-Hydroxycleroda-3,13-dien-15,16-olide (HCD) and its analogs extracted from the bark of P. longifolia have strong anti-inflammatory activity [ 99 ]. The enhanced expression of cyto-protective HO-1 factor and anti-inflammatory enzyme in microglia has been reported [ 100 ].…”
Section: Underlying Mechanisms Of Natural Compound-induced Autophamentioning
confidence: 99%
“…These chemical shifts were very similar to those of clerodane diterpenes with a γ-hydroxyl butenolide group. [17][18][19] The connection between the hexahydroindene skeleton and the hydroxyl butenolide group was assisted by a two-atom aliphatic chain whose signals appeared as cross peaks between H-11 and H-12 in (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%